Effect of Standardised Extract Pegagan Embun (Hydrocotyle sibthorpioides Lam.) toward Natural Killer Cell and CD8 Cell Activities on White Male Mice Exposed to H5N1 Virus Antigen - Afriwardi, Afriwardi; Wahyuni, Fitratul; Husni, Elidahanum; Alianta, Aditya Alqamal; Aldi, Yufri (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: Community in Indonesia used pegagan embun (Hydrocotyle sibthorpioides Lam.) to increase endurance. Based on that, the study aimed to determine the effects of pegagan embun extract on natural killer (NK) cells and CD8 cells activities in white male mice exposed to the H5N1 antigen. MATERIALS AND METHODS: As many as thirty-five experimental white male mice were used, divided into seven groups, by varying the time of administration of the H5N1 antigen. Groups I and II, were given the test extract for 7 days and induced H5N1 antigen on days 1 and 7, then evaluated on day 8. Group III was given a test extract for 3 days, then induced antigen on the 4th day and continued with giving the test extract until day 7th. In Groups V and VII, only H5N1 antigen induction on day 1 and evaluated on day 8. Groups IV and VI were given the test extract for 7 and 4 days. The observations examine the activities of NK cells and CD8 cells. The data were analyzed with a one-way analysis of variation method with p = 0.05, then analyzed with Duncan Multiple Range Test. RESULTS AND DISCUSSION: After calculating, the NK cell activity for groups 1 to 7, respectively: 2.12; 2.03; 2.07; 1.87; 1.98; 1.91; and 1.95 ng/mL while for CD8 cell activity 22.23; 24.61; 23.69; 21.10; 19,20; 19.87; and 18.13 ng/mL. The results showed that giving pegagan embun extract to white male mice exposed to the H5N1 antigen increase the activities of NK cells and CD8 cells. CONCLUSION: It concluded that administration of standardized extract of pegagan embun (H. sibthorpioides Lam.) at a dose of 200 mg/kg BW increased NK cells activities and CD8 cells of white male mice exposed to H5N1 virus antigen.